Efeito da suplementação com astaxantina na qualidade oocitária e desenvolvimento in vitro de embriões de vacas holandesas durante o verão - Costa, Rafael Arcenio da (2021)
Lactating cows in Brazil are frequently exposed to high temperatures, especially during the summer. Subjected to the effects of heat stress, they develop reproductive problems like impaired follicular growth, negatively impacting oocyte quality. This is particularly relevant for high-yielding Holstein cows. In this manner, this study aimed to examine the effect of daily supplementation of milk cows with astaxanthin on oocyte quality and in vitro embryo developmental potential. Lactating Holstein cows (n = 45; ± 550 kg of body weight) from a Compost Barn in the Southwest region of Paraná - Brazil were treated with astaxanthin (0, 0.25 or 0.50 mg kg-1 day-1 for control, low astaxanthin or high astaxanthin group, respectively) for 75 days. Upon the end of the supplementation period, three OPU with a 15-day interval were conducted for oocyte quality analysis in all females. All oocytes were then subjected to in vitro fertilization to assess their developmental potential. Data were tested for normality of residues (Shapiro-Wilk test) and homogeneity of variances (F max test), and square roottransformed when premises for ANOVA were not met. One-way ANOVA (embryo development data; effect of astaxanthin) or two-way repeated-measures ANOVA (oocyte quality, effect of astaxanthin, time, and interaction) followed by Tukey’s multiple comparisons test were performed using GraphPad Prism vs.7.0 (GraphPad Inc.). Although elevated temperatures were observed during all summer, mainly on afternoons with the maximum temperature of 29 ºC detected in the compost barn, skin and rectal temperatures, heart, and respiratory rates were not significantly affected. Nevertheless, a clear effect of the season was observed on in vitro embryo production when oocytes were aspirated from control females at different times of the year. A lower blastocyst rate was obtained during the summer (p=0.0399). A higher total oocyte recovery rate was obtained when cows supplemented with 0.50 mg kg-1 day-1 astaxanthin (p<0.05) were aspirated compared to control (p=0.0395) and 0.25 mg kg1 day-1 astaxanthin (p=0.0279) groups. However, such effect was only detected on the very first OPU, diminishing with time after astaxanthin supplementation ended. Moreover, a higher dose of astaxanthin allowed the collection of more morphologically viable oocytes when compared to the low astaxanthin group (p=0.0452). Finally, cleavage (D3) and blastocyst (D7) rates were not affected by astaxanthin supplementation. The same was observed for development and hatching rates. In conclusion, although the supplementation of lactating Holstein cows with astaxanthin for 75 days in the summer can improve the total and viable oocyte recovery rates, it could not bring the embryo production rates closer to the higher rates observed in the winter. Therefore, further studies associating animal handling, confinement systems, environment management, and the use of the antioxidant astaxanthin are needed to contribute to the improvement of reproductive success rates in dairy cows in the summer.